Student engagement in English language learning with artificial intelligence (AI) chatbot from theory of planned behavior perspective - Fauziah Fauziah; Novita Diana; Silvia Putri; Teuku Fadhli (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Artificial Intelligence (AI) chatbots have been widely integrated into English learning and teaching, but qualitative evidence portraying the students’ engagements and the socio-behavior factors shaping the engagement remains scarce. Guided by the theory of Planned Behavior (TPB), this narrative inquiry investigated student engagement in English language learning facilitated by AI chatbots. This study explores the lived experiences and perceptions of fifteen participants enrolled in a private Islamic higher education institution in Aceh, Indonesia. Semi-structured interviews and focus group discussions were selected to explore students’ attitudes, social influences, and perceived behavioral control. Thematic analysis with coding aligned to TPB constructs (attitudes, subjective norms, and perceived behavioral control) and engagement dimensions (behavioral, cognitive, and emotional) was applied. Additionally, this study emphasizes the importance of considering sociocultural contexts and user experience in the design and implementation of AI-driven educational tools. The findings support previous research highlighting the importance of user attitudes, social influences, and perceived control in shaping students’ engagements with technology in educational contexts. The insights gleaned from this research contribute to the broader discourse on technology-mediated language learning and inform strategies for enhancing student engagement in English language education.